Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Beban Kerja Terhadap Kinerja Pegawai UPT Puskesmas Klakah Kabupaten Lumajang - Devira Azzahroh (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine The Influence of Work Environment, Work Discipline, and Workload on Employee Performance at UPT Puskesmas Klakah, Lumajang Regency. The research design employed is exploratory research using a saturated sampling technique. The research instrument was a questionnaire distributed directly to 70 employees as respondents. The collected data were analyzed using Multiple Linear Regression Analysis with the assistance of SPSS version 27. Based on the results, it was found that: 1) The work environment has a positive and significant effect on employee performance. 2) Work discipline has a positive and significant effect on employee performance. 3) Workload has a negative and insignificant effect on employee performance.
Reupload file repositori 12 mei 2026_Firli_Tata :: Finalisasi Repositori File 12 Mei 2026_Kurnadi
Keywords: Work Environment; Work Discipline; Workload; Employee Performance